Glanzmann thrombasthenia in Pakistan: molecular analysis and identification of novel mutations. Issue 2 (15th July 2015) - Haghighi, A.; Borhany, M.; Ghazi, A.; Edwards, N.; Tabaksert, A.; Haghighi, A.; Fatima, N.; Shamsi, T.S.; Sayer, J.A.
Abstract : Glanzmann thrombasthenia (GT) is an inherited genetic disorder affecting platelets, which is characterized by spontaneous mucocutaneous bleeding and abnormally prolonged bleeding in response to injury or trauma. The underlying defect is failure of platelet aggregation due to qualitative and/or quantitative deficiency of platelet integrin αIIbβ3 resulting from molecular genetic defects in either ITGA2B or ITGB3 . Here, we examine a Pakistani cohort of 15 patients with clinical symptoms of GT who underwent laboratory and molecular genetic analysis. In patients with a broad range of disease severity and age of presentation, we identified pathogenic mutations in ITGA2B in 11 patients from 8 different families, including 2 novel homozygous mutations and 1 novel heterozygous mutation. Mutations in ITGB3 were identified in 4 patients from 3 families, two of which were novel homozygous truncating mutations. A molecular genetic diagnosis was established in 11 families with GT, including 5 novel mutations extending the spectrum of mutations in this disease within a region of the world where little is known about the incidence of GT. Mutational analysis is a key component of a complete diagnosis of GT and allows appropriate management and screening of other family members to be performed.